Biocontrol Effect and Possible Mechanism of Food-Borne Sulfide 3-Methylthio-1-Propanol Against Botrytis cinerea in Postharvest Tomato - Feng, Shun; Lu, Wang; Jian, Yongfei; Chen, Yu; Meng, Run; Deng, Jie; Liu, Qing; Yu, Tingting; Jin, Liang; Yang, Xingyong; Li, Zhengguo; Jian, Wei (Frontiers in Plant Science, 2021)
Botrytis cinerea is one of the most destructive fungal pathogens causing tremendous losses in fresh fruit or vegetables. 3-methylthio-1-propanol (3-MP) is a naturally occurring food-borne sulfide, which is mainly used to increase the flavor in food. However, the potential application of 3-MP in the postharvest phase to manage fruit fungal diseases has not been explored. In this study, the antifungal activity of 3-MP against B. cinerea was evaluated, and the possible mechanism involved was explored. In vitro, 3-MP treatment could effectively inhibit the mycelial growth, spore germination and germ tube elongation of B. cinerea. 3-MP also impaired the spore viability and membrane integrity of B. cinerea, as well as increased the leakage of nucleic acids, proteins, and malondialdehyde (MDA) in B. cinerea. In vivo, 3-MP fumigation treatment inhibited the infection of B. cinerea on tomato fruits. And the fruits with 3-MP fumigation treatment exhibited higher antioxidant enzyme activity, lower MDA content, as well as a significant delay of induction of the expression of most of the stress-related genes when compared to the control group. Moreover, a cytotoxicity evaluation revealed that 3-MP had no toxicity to normal cells in a certain concentration range. Collectively, our research results will provide evidence for the development of food-borne sulfide 3-MP as a fungicide in food and agriculture, and provide an important reference for the formulation of B. cinerea biocontrol strategies.